React: up & running : building web applications - Stefanov, Stoyan (O'Reilly Media, 2016)
"Hit the ground running with React, the open-source technology from Facebook for building rich web applications fast. With this practical guide, Facebook engineer Stoyan Stefanov teaches you how to build components--React's basic building blocks--and organize them into maintainable, large-scale apps. If you're familiar with basic JavaScript syntax, you're ready to get started. Once you understand how React works, you'll build a complete custom Whinepad app that helps users rate wines and keep notes. You'll quickly learn why some developers consider React the key to the web app development puzzle." --